Comparative proteomics of sugarcane smut fungus- Sporisorium scitamineum unravels dynamic proteomic alterations during the dimorphic transition - Kumaravel, Nalayeni; Ebinezer, Leonard Barnabas; Ashwin, N. M. R.; Franchin, Cinzia; Battisti, Ilaria; Carletti, Paolo; Sundar, Amalraj Ramesh; Masi, Antonio; Malathi, Palaniyandi; Viswanathan, Rasappa; Arrigoni, Giorgio (Journal of Proteomics, 2024)
Life cycle of the dimorphic sugarcane smut fungi, Sporisorium scitamineum , involves recognition and mating of compatible saprophytic yeast -like haploid sporidia (MAT -1 and MAT -2) that upon fusion, develop into infective dikaryotic mycelia. Although the dimorphic transition is intrinsically linked with the pathogenicity and virulence of S. scitamineum , it has never been studied using a proteomic approach. In the present study, an iTRAQ-based comparative proteomic analysis of three distinct stages was carried out. The stages were: the dimorphic transition period - haploid sporidial stage (MAT -1 and MAT -2); the transition phase (24 h post co -culturing (hpc)) and the dikaryotic mycelial stage (48 hpc). Functional categorization of differentially abundant proteins showed that the most altered biological processes were energy production, primary metabolism, especially, carbohydrate, amino acid, fatty acid, followed by translation, post -translation and protein turnover. Several differentially abundant proteins (DAPs), especially in the dikaryotic mycelial stage were predicted as effectors. Taken together, key molecular mechanisms underpinning the dimorphic transition in S. scitamineum at the proteome level were highlighted. The catalogue of stage -specific and dimorphic transition -associated -proteins and potential effectors identified herein represents a list of potential candidates for defective mutant screening to elucidate their functional role in the dimorphic transition and pathogenicity in S. scitamineum . Biological significance: Being the first comparative proteomics analysis of S. scitamineum , this study comprehensively examined three pivotal life cycle stages of the pathogen: the non-pathogenic haploid phase, the transition phase, and the pathogenic dikaryotic mycelial stage. While previous studies have reported the sugarcane and S. scitamineum interactions, this study endeavored to specifically identify the proteins responsible for pathogenicity. By analyzing the proteomic alterations between the haploid and dikaryotic mycelial phases, the study revealed significant changes in metabolic pathway -associated proteins linked to energy production, notably oxidative phosphorylation, and the citrate cycle. Furthermore, this study successfully identified key metabolic pathways that undergo reprogramming during the transition from the non-pathogenic to the pathogenic stage. The study also deciphered the underlying mechanisms driving the morphological and physiological alterations crucial for the S. scitamineum virulence. By studying its life cycle stages, identifying the key metabolic pathways and stage -specific proteins, it provides unprecedented insights into the pathogenicity and potential avenues for intervention. As proteomics continues to advance, such studies pave the way for a deeper understanding of plantpathogen interactions and the development of innovative strategies to mitigate the impact of devastating pathogens like S. scitamineum.
Keywords: dimorphism; fungi; iTRAQ; Smut; Sugarcane; Virulence

Transient expression of small secreted proteins of colletotrichum falcatum elicits broad-spectrum disease resistance in tobacco - Amalamol, Dharmaraj; Ashwin, N. M. R.; Lakshana, Kana Valiyaveettil; Ramesh Sundar, Amalraj; Jeevalatha, A.; Ramesh, R.; Malathi, P.; Viswanathan, R. (Plant Cell Reports, 2026)
Small secreted proteins (SSPs) play crucial roles in pathogenicity and host manipulation. C. falcatum, the causative agent of red rot in sugarcane, secretes numerous SSPs during its interaction with the host. In this study, three abundantly secreted SSPs of C. falcatum-CfEPL1 (eliciting plant response-like protein 1), CfPDIP1 (plant defence inducing protein 1), and CfBYS1 (Blastomyces yeast phase-specific protein 1) were transiently expressed in the model system, Nicotiana tabacum, to delineate their functional roles. Upon co-expression with green fluorescent protein (GFP), fluorescence signals of all three SSPs were predominant in the apoplastic spaces, consistent with the localisation predictions. Among the three SSPs, transient expression of CfEPL1 and CfPDIP1 induced a hypersensitivity response (HR), reactive oxygen species (ROS) production, and callose deposition in the infiltrated regions. However, transient expression of CfBYS1 triggered neither visible HR nor prominent upregulation of defence-related genes. Transcription profiling of defence-related genes in N. tabacum leaves infiltrated with CfEPL1 and CfPDIP1 indicated an upregulation of various genes associated with systemic acquired resistance (SAR), salicylic acid (SA), and jasmonic acid (JA) pathways. Inoculation of Pseudomonas syringae pv. tomato DC3000 (Pto) at the site of CfEPL1 and CfPDIP1 infiltration resulted in attenuated disease lesion development. Similarly, a reduction in bacterial wilt disease severity was observed, when the vacuum-infiltrated tobacco plants were challenged with Ralstonia solanacearum, which was substantiated by pathogen biomass quantification and SAR-associated marker expression profiling. Overall, this study demonstrated that the two SSPs, CfEPL1 and CfPDIP1, could confer broad-spectrum disease resistance in N. tabacum. [GRAPHICS]
Keywords: PAMP; Small secreted proteins; systemic acquired resistance; Transient expression